(3eNJUQ GdgOi GdfHhis - (3eMeO Hf YHO GdhgGH Hf SdjeGf GdJejej GdfLOj,J (B1206 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aEf Gddg SHMGfg gh GdeJaQO HGdNdb hGdENJjGQ s
(3BNQgG (B:s
(3hPcQ GdJQePi hMSfg Yfg Cf GdYHO EPG GJRhL HZjQ EPf ehGdjg agh YGgQ GfJgi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B257s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs